Beasts of place and time: animals and Britishness in popular natural history, c. 1760-1860 - Carter, Matthew (2023)
This study focuses on the period 1760 to 1860, a time when popular interest in natural history was significantly increasing in Britain, as technological innovations and evolving socio-economic conditions fuelled the growth of popular natural history media aimed at wealthy British urbanites. Through advances in printing, British popular natural history literature became increasingly available, whilst improvements in travel, transportation and preservation techniques all helped to facilitate the growth of exotic animal exhibitions and taxidermy displays. Consequently, popular audiences were able to engage with natural history through a diverse range of intersecting opportunities that centred round a single, congruent body of animal knowledge. This thesis demonstrates how, within this context, conceptualisations of animals contained expressions of Britishness that helped to reinforce particular imaginings of a superior national character that was rooted in notions of modernity and tied to claims of rationality, ingenuity, commercial acumen and benevolence. These imaginings of Britishness, frequently articulated as an expansion of Englishness extending beyond England’s borders to include non-English groups within a single, English-led, cultural hegemony, were frequently communicated through the locating of animals in space and time, which formed a core element of animal conceptualisations.